LDPC-coded unitary space-time modulation with low-complexity iterative demodulate-decoding scheme - Li-jiao WANG; Lin ZHANG; Ling-ling YANG; Li PENG; Da-wei FU (Tongxin xuebao)
A practical low-density parity-check(LDPC) coded unitary space-time modulation (USTM) noncoherent MIMO communication system over Rayleigh flat fading and additive white Gaussian noise (AWGN) channel was con-structed, where the LDPC code is selected from IEEE 802.16e Standard and USTM is constructed by the unitary matrix based on the sinc-cosinc function, SC-USTM for short. At the receiver, the maximum a posteriori probability (MAP) de-modulating algorithm of the SC-USTM was first designed; for reducing the complexity of MAP demodulator, the dual demodulator was then conceived; for improving the performance, the iterative feedback between the belief propagation (BP) decoder and the MPA demodulator was finally introduced. The simulation test shows that the system of the LDPC coded SC-USTM is superior to the uncoded SC-USTM about 15～17 dB at BER10−5, and this system has very low complexity.